2011
DOI: 10.1128/aem.00195-11
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Edwardsiella ictaluri Type III Secretion System by pH and Phosphate Concentration through EsrA, EsrB, and EsrC

Abstract: A recently described Edwardsiella ictaluri type III secretion system (T3SS) with functional similarity to the Salmonella pathogenicity island 2 T3SS is required for replication in channel catfish head-kidney-derived macrophages (HKDM) and virulence in channel catfish. Quantitative PCR and Western blotting identified low pH and phosphate limitation as conducive to expression of the E. ictaluri T3SS, growth conditions that mimic the phagosomal environment. Mutagenesis studies demonstrated that expression is unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
57
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 53 publications
(68 reference statements)
2
57
0
Order By: Relevance
“…8), as documented in E. ictaluri and E. tarda. 35,36,37 Our data support the idea that the regulatory circuits of SsrB/EsrB family proteins have been well conserved during evolution (Fig. 4G).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…8), as documented in E. ictaluri and E. tarda. 35,36,37 Our data support the idea that the regulatory circuits of SsrB/EsrB family proteins have been well conserved during evolution (Fig. 4G).…”
Section: Discussionsupporting
confidence: 77%
“…31 Like their counterparts SsrA, SsrB and SPI-2 in Salmonella, 32,33,34 EsrA and EsrB and the associated T3SS locus may be horizontally acquired and may have evolved to coordinate the expression of virulence and adaptation to host microenvironments by the reprogramming of ancestral genes unlinked to the T3SS locus. 6 Although the exact stimulus recognized by HK EsrA remains elusive, 35 EsrA-EsrB plays a key role in regulating the expression and secretion of T3SS and T6SS by directly binding to the promoters of T3SS genes and to that of EsrC, which further regulates the expression of other T3SS and T6SS genes in the bacterium. 22,36,37 It is still unknown whether other genes, especially those associated with the invasion process, and their regulatory mechanisms are controlled by EsrB during in vivo and in vitro infection of hosts.…”
Section: Introductionmentioning
confidence: 99%
“…EseI was also secreted, as detected in cytosol fraction, but its secretion was not dependent upon the T3SS, and this protein was not affected by the regulator proteins EsrBC in the E. ictaluri T3SS, as reported by Rogge and Thune (2011), which is of interest for further research. The secretion of EseH and EseI may then be deployed by E. ictaluri to interfere with host cells.…”
Section: Discussionmentioning
confidence: 74%
“…The secretion of EseH and EseI may then be deployed by E. ictaluri to interfere with host cells. Using quantitative and Western blotting analyses, Rogge and Thune (2011) found that low pH and phosphate limitation was conducive to an active T3SS in E. ictaluri, whereas they failed to detect Flag-tagged EseH. The 70-99% similarity in 33 ORFs of T3SS between E. tarda and E. ictaluri may enable the functional identification of T3SS molecules in the E. tarda surrogate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation